Structural Design of The Building Grand Diara Cileungsi Hotel 10 Floor - Purwanto, Doni; Hanun, Yunan; Rutama, Dedy (Journal of Global Engineering Research and Science, 2023)
Hotel buildings are tall buildings that have a fairly complex design. This research will discuss the design of the upper structure of the Grand Diara Cileungsi hotel building including beams, columns, and floor plates. The design of this upper structure also takes into account the loads acting on the structure such as dead loads, live loads, and earthquake loads by using a moment-bearing frame system. This building is designed based on SNI 2847-2019 and SNI 1726-2019 to design earthquake-resistant buildings. The building structure design stage begins with the collection of structural design data which is then modeled in ETABS 19.0.2 software. After modeling in ETABS software, the design recommendations on concrete structures are as follows; 120 mm thick plate with a ratio of (0.79%), 100 mm thick plate for the roof with a ratio of (0.65%) Main Beam (350 x 650 mm with a ratio of 1.34%), Child Beam (300 x 500 mm with a ratio of 0.67%), Child beam (300 x 500 mm with a ratio of 0.67%). 67%) and sub-beams (250 x 350 mm with a ratio of 0.67%), (Concrete columns 600 x 600 mm with a ratio of 1.29%) and (400 x 400 mm with a ratio of 1.93%) with concrete quality (fc') = 30 Mpa and flexural reinforcement quality is (fy) = 420 Mpa.